Efficiency, Efficiency or Efficiency in public works - road infrastructure of the Cardinal District (2016)
This paper aims to present the current situation in the execution of works in the Capital District from one limited aspect and what has been its development under the framework of the urban development of the city, as well as how the various projects are financed and the benefits that must be provided to the population under the premise that all citizens contribute according to their economic capacity to fulfill the goals of the State , finally as the public resources are managed by reference district administrations to investment in projects work planned for the city. The proposal made globally on the new way of thinking about the development of public goods and services, where the state without neglecting the concept of " public " allows the private sector not only as executor of exposed but with public works investment from these, working for the achievement of general and particular benefit.